O Liniowej Teorii Powłok o Malej Wyniosłości - Pietraszkiewicz, W. (Engineering Transactions, 1967)
This paper presents an accurate linear theory of shallow shells, based on the conceptions of Green and Zerna [1]. All the vector relations are expressed in consistent manner using the basic vectors of the plane projection of the shell and taking into account the geometrical and physical assumptions concerning the shallowness of the shell. The obtained fundamental equations are solved in displacements, in stresses functions and by a mixed method. With the additional assumption of small variability of curvature, each of the three methods reduces to the solution of the same complex differential equation of the fourth order the difference being that of the particular integral.